EXPLORING TEACHERS' RESILIENCE IN INDONESIAN EFL LEARNING CONTEXTS - Kristian Florensio Wijaya (LET: Linguistics, Literature and English Teaching Journal, 2021)
To promote more holistic, pleasurable, and meaningful ELT enterprises requires specific durable psychological characteristics from EFL teachers in terms of positive emotions, well-being, robust motivation, and resilience. The ultimate psychological stream is noted as one of the paramount factors embodying brighter future educational outlooks since the majority of prior studies revealed that a higher degree of resilience would enable EFL teachers to cultivate stronger dedication, tenacity, and commitment in leading their pupils to reach the targeted learning outcomes fully. In consonance with this theoretical underpinning, the major focus of this present study is to unearth particular independent strategies employed by two invited EFL teachers in maintaining their resilience, particularly while being exposed to adverse working conditions and unpredictable stress events. Thus, the results obtained from these two invited participants will shed a new light regarding a set of rewarding independent strategies incorporated by EFL teachers in preserving their resilience amid taxing working conditions. In light of this matter, the sharing emanated from these research participants will work as a propelling force for global EFL teachers working under arduous teaching dynamics owing to the full activation of their resilience enabling them to stay on the right educational tracks; educating young generations for better future lives.